Efektifitas Air Madu dan Air Gula Untuk Meningkatkan Power Pada Persalinan Kala II - Yusri Dwi Lestari; S eptin Putri Pramudita (Ovary Midwifery Journal, 2020)
Prolonged labor, also called"dystocia", defined asan abnormallabor/difficult. abnormalitiesdue to power (his disorder). Therefore, researc herswanted to know the differen cebeforeand after administration of honey water, before and after administration of sugar water to increase the power in the second stage of labor, in BPS Sri Wahyuningsi, Amd.Keb. This study was conducted with type-Quasy Experimental research design (quasi-experimental) with the analytic study design in July 2014 in Sri Wahyuningsih BPS, Amd.Keb, District Panarukan Situbondo, witha population of maternal second stage. Nonequivalent sampling time sample design, while the variables use dareh oney and sugarwater to power the delivery process. Retrieval of data through direct observation sheet. Governance witha paired t test, oneway ANOVA through SPSS software version 16.0. Results of the study can be seen that the water is more effective than sugar water honey to increase the power in the mother. Conclusion The above data is doneusing the comparativestatistical test with paired T test via SPSS computeras sistance. From the result singet 0,003 results < (0.05).So the conclusion is Horejected, there is a difference between before and after agiven honey water given honey water, and given sugar water before and after administration of sugar watessr. From the results of bothie, after the wateris given honey and sugar water were test edstatisti callyusing Oneway Anova resultsdi can 0.272 > (0.05) so that the conclusion is Harejected, there is no difference between honey and water given sugar water.